The Impact of CRM dimensions on Customer Retention in the Hospitality Industry: Evidence from the Moroccan Hotel sector - Chetioui, Youssef (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
Customer relationship management (CRM) has currently become one of the most controversial issues and is considered by many marketers as a focal-center in the business field. Previous literature suggest that it is essential for hotels to adopt CRM technologies to help hotel managers improve their organizations performance. Nevertheless, the relationship between CRM technology and hotel performance is still ambiguous. In an attempt to review the different perspectives of CRM, this research paper focus on the view that suggests that CRM implementations typically involve the four dimensions: (1) customer orientation (2) knowledge management (3) CRM organization, and (4) CRM technology. Our study evaluates the relationship between CRM dimensions and hotel performance (customer retention) in Morocco. A sample of 80 Moroccan hotels was examined, and regression and other tests were used for analyses and testing. Our findings demonstrates a significant effect of customer orientation, knowledge management, and CRM organization on customer retention. While the use of CRM technology has been demonstrated to not significantly affect customer retention in surveyed hotels.